2012
DOI: 10.1128/aac.05244-11
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Related Effects on Tenofovir Pharmacokinetics: a Population Study with 186 Women

Abstract: According to the European AIDS Clinical Society, tenofovir disoproxil fumarate can be used in HIV-infected pregnant women if started prior to pregnancy, although no data are available on the pharmacokinetics of tenofovir (TFV) during pregnancy. The aim of this study was to describe TFV pharmacokinetics in HIV-infected women and to evaluate the effect of pregnancy on TFV disposition. Samples were collected according to a therapeutic drug monitoring in 186 women, including 46 pregnant women treated with TFV and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
47
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 13 publications
9
47
1
Order By: Relevance
“…Creatinine clearance was a significant covariate of clearance and is biologically meaningful because tenofovir is a renally cleared drug. The population pharmacokinetic parameters are in general agreement with those in previous reports (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Creatinine clearance was a significant covariate of clearance and is biologically meaningful because tenofovir is a renally cleared drug. The population pharmacokinetic parameters are in general agreement with those in previous reports (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Discussionsupporting
confidence: 81%
“…However, reliable dosing records and informative pharmacokinetic sampling are important for unbiased pharmacokinetic parameter estimation. Several population pharmacokinetic models for tenofovir have been reported (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). However, all of them include data from HIV-1-infected subjects or a mix of healthy and HIV-infected subjects (7), except for our recent reports on a population of healthy women (15,16).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…A study in lactating rhesus macaques showed that tenofovir concentrations in breast milk corresponded to 20 % of the serum values [46]. After maternal tenofovir injection, human breast milk concentrations of tenofovir are very low and it has been calculated that nursing infants would be exposed to less than 2 % of the oral infant therapeutic dose [47]. Overall these findings are very reassuring and should be discussed with a mother in the context of her wishes about breastfeeding and the plans to continue tenofovir post-partum.…”
Section: Safety Of Direct Acting Antiviral Therapy In Pregnancy and Bmentioning
confidence: 99%
“…Renal excretion of didanosine is increased in pregnancy, but dose alteration is probably not required [108]. Tenofovir concentrations in the third trimester were reported to be reduced by about 15% compared with postpartum, but trough levels are adequate [109] although in a population-based study of tenofovir use, pregnant women appear to have 39% more clearance than non-pregnant women [110]. Higher rates of treatment failure during pregnancy with tenofovir-containing combinations have not been reported.…”
Section: Grading: 1cmentioning
confidence: 99%